In silico and Histochemical Analysis of Soursop Leaves (Annona muricata) Against Alpha Estrogen Receptor - Afidah Fajar Nuari; Gatra Ervi Jayanti; Majida Ramadhan (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Soursop leaves (Annona muricata) are known as a plant that has the potential to treat breast cancer, which has a high mortality rate in women in Indonesia. The receptor that plays the most important role in breast cancer development is the Estrogen Receptor Alpha (ERa). This study aims to identify active compounds in soursop leaves that have the potential to inhibit breast cancer cell growth through in silico analysis using molecular docking of the ER? receptor using KNApSAck, PASS Online, PubChem, PDB ID, PyRx, and Discovery Studio software and Histochemical analysis was performed using fresh soursop leaves by making an incision on the lower part of the leaf and adding reagents AlCl, FeCl, Na2CO, CuSO4, glycerin, Wagner reagent, immersion oil, and ethanol, then observed microscopically. The in silico results showed the presence of specific compounds from soursop leaves and one reference compound (OHT600). Cis-Solamin had the highest binding affinity (-9.3 kcal/mol), better than the native ligand (-7.6 kcal/mol), and interacted with the amino acid Glutamine 532 (GLU532). Histochemical analysis showed the content of flavonoids, phenols, tannins, terpenoids, and alkaloids, accompanied by color changes in trichome and stomatal tissues. Based on the research data, it was concluded that soursop leaves can inhibit the growth of breast cancer cells through the content of secondary metabolites that actively inhibit Er? receptors.